Kajian Yuridis Kemerdekaan Pers di Era Pembaharuan Hukum Pidana Terhadap Pasal Penghinaan Terhadap Pemerintah - Reza Seby Alfikri; Muhammad Ilham Adi Nugroho; Ayu Putriyana (GLOBAL SCIENTS PUBLISHER, 2025)
The Press Law stipulates that the press has a very important role in conveying information, providing education, presenting entertainment, and carrying out social control functions. The method used is the normative research method. This article examines how the legal analysis of Law Number 1 of 2023 concerning insults to the government or state institutions regarding press freedom in Indonesia and also how the relationship between the government or state institutions and supervision carried out by the public in the legal system and democracy in Indonesia. The results of the study, namely Articles 240 and 241 of Law Number 1 of 2023 on the Criminal Code contain the potential for conflict with press freedom guaranteed in the constitution. Public supervision of the government and state institutions in Indonesia is an important element in maintaining transparency, accountability, and stability of democracy.